The Relationship Between Racial Identity and Perceived Significance of the Election of President Barack Obama Among African American Mothers. Issue 3 (2nd July 2016) - Franco, Marisa; Smith-Bynum, Mia
ABSTRACT: African American women's racial identity is a major determinant for how they interpret the world around them, yet there is little research examining how specific aspects of racial identity are linked with attitudes about an event that has been highly significant for African Americans: the election of President Barack Obama. The present study examines the relationship between African American mothers' racial identity and their perceived significance of the election of President Barack Obama as an indicator of reduced systemic and actual racism for African Americans, using a sample of 110 African American mothers residing in a Northeastern metropolitan area. Results revealed that racial centrality and assimilation positively predicted perceived significance of President Obama's election for diminishing racism. Implications and future directions are discussed.